Desain Dakwah Ustadz Hanan Attaki melalui Media Sosial Instagram @ayah_amanah - Ismiati, Ismiati; Sofiatin, Sofiatin; Zuhriyah, Luluk Fikri (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2024)
The purpose of this study is to examine the design of millennial da'wah Ustadz Hanan Attaki in an Instagram social media account under the name @ayah_amanah, such as da'wah strategies, delivery methods, mad'u targets, and message choices conveyed by Ustadz Hanan Attaki. Using a descriptive qualitative research approach, as well as data deepening with observation, interview, and social media content analysis methods. The results of the research illustrate that Ustadz Hanan Attaki in this @ayah_amanah Instagram social media preaches directly from city to city which is then documented and uploaded through @ayah_amanah Instagram account.Â For the da'wah strategy used by Ustadz Hanan Attaki, namely persuasive and sentimental da'wah, namely preaching by captivating the hearts of mad'u, as evidenced by the messages and themes chosen in his study are light, easy to understand, use millennial language, and are considered in accordance with the condition of the target da'wah, namely young people. The implication in this study is to provide a reference for da'wah in the latest way and follow digital developments, da'wah is designed to be flexible, relaxed, and creative.